PENERAPAN MODEL PEMBELAJARAN KONSTRUKTIVISME UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS X PADA MATA PELAJARAN GEOGRAFI DENGAN MATERI LITOSFER DI SMA NEGERI 34 HALMAHERA SELATAN - Darling Surya Alnursa (Program Studi Pendidikan Ekonomi Institut Sain dan Kependidikan (ISDIK) Kie Raha Maluku Utara, 2026)
Classroom action research is a form of reflective research that involves taking specific actions to improve or enhance classroom learning practices in a professional manner. The purpose of this study is to determine the improvement in learning outcomes of tenth-grade students using the Constructivist learning model on the Lithosphere topic at State Senior High School 34, South Halmahera. This type of research uses Classroom Action Research (CAR). Based on the research results, the application of the constructivist learning model in tenth-grade students at State Senior High School 34, South Halmahera, has been proven to improve the quality of the learning process and outcomes. This is demonstrated by the increased activity of teachers and students during the learning process, as reflected in the percentage of activity in each cycle. Furthermore, the application of the constructivist learning model also successfully improved student learning outcomes, as demonstrated by an increase in the percentage of learning completion from 52% in Cycle I to 81% in Cycle II. Thus, the constructivist learning model is effective in increasing student activity and learning outcomes in the subject studied.